2012
DOI: 10.1080/02640414.2011.647706
|View full text |Cite
|
Sign up to set email alerts
|

Childhood aerobic fitness predicts cognitive performance one year later

Abstract: Aerobically fit children outperform less fit peers on cognitive control challenges that involve inhibition, cognitive flexibility, and working memory. The aim of this study was to determine whether, compared with less fit children, more fit 9- and 10-year-old pre-adolescents exhibit superior performance on a modified compatible and incompatible flanker task of cognitive control at the initial time of fitness testing and approximately one year later. We found that more fit children demonstrated increased flanke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
141
4
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(175 citation statements)
references
References 53 publications
13
141
4
17
Order By: Relevance
“…Su sveikata susijęs fi zinis aktyvumas, pavyzdžiui, pastovus dalyvavimas fi zinėje veikloje ir su tuo susijęs didesnis aerobinio pajėgumo lygis, yra susiję su geresniais mokymosi pasiekimais (Chaddock et al, 2012). Tyrimais nustatyta, kad tie mokiniai, kurie būdavo aktyvesni mokykloje ir savaitgaliais, demonstravo geresnius skaitymo, matematikos pasiekimus (Donnelly et al, 2009).…”
Section: Rezultatų Aptarimasunclassified
“…Su sveikata susijęs fi zinis aktyvumas, pavyzdžiui, pastovus dalyvavimas fi zinėje veikloje ir su tuo susijęs didesnis aerobinio pajėgumo lygis, yra susiję su geresniais mokymosi pasiekimais (Chaddock et al, 2012). Tyrimais nustatyta, kad tie mokiniai, kurie būdavo aktyvesni mokykloje ir savaitgaliais, demonstravo geresnius skaitymo, matematikos pasiekimus (Donnelly et al, 2009).…”
Section: Rezultatų Aptarimasunclassified
“…Participaram da intervenção todos os alunos regularmente matriculados no BIA, porém, para ser incluída na analise final do estudo a criança deveria ter participado de todas as aulas, bem como, das avaliações no pré-intervenção e pós--teste; estar entre os estágios 1 e 2 da escala de Tanner (1962) (Chaddock et al, 2012;Voss et al, 2011;Pontifex et al, 2010) Cardeal, L.A. Pereira, P.F. Silva, N.M Já na última fase, a palavra em destaque está escrita com cor diferente em relação ao nome.…”
Section: Critérios De Inclusãounclassified
“…For healthy older adults (N = 179, 66.6 ± 5.6 years), Verstynen and colleagues 38 found (by means of the same analysis tool as Chaddock and colleagues 34,36 ) that higher cardiovascular fitness levels correlated positively with taskswitching performance and thus with cognitive flexibility. Furthermore, the volumes of the caudate nucleus, the putamen and the globus pallidus were positively related to task-switching performance as well.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…Chaddock and colleagues 34 concluded that the association between the volume of the dorsal striatum and the cognitive control performance supports the assumption that these nuclei are also involved in motor integration and response resolution. In a follow-up study, Chaddock and colleagues 36 found that approximately one year later, the high-fit children still showed superior performance in the Flanker task compared to the low-fit children. The authors attributed these better cognitive performances to the previously measured higher fitness levels and to the greater volumes of the putamen and globus pallidus measured one year earlier.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%